Correlação entre a redução do peso corporal e o balanço símpato-vagal após a cirurgia bariátrica - Lucas, Cristina Maria de Souza (2016)
Introduction: Obesity is a growing public health problem in the population and is associated with increased cardiovascular vulnerability. It has long been known that there is a direct relationship between the amount of fat and blood pressure and heart rate. Studies have shown that obese individuals have a predominance of sympathetic activity, which is strongly associated with increased blood pressure and heart rate thus leading to increased cardiovascular risk compared to individuals of the same age and not obese. The aim in this study was to correlate the reduction of the body fat in morbid obese patients 3 and 6 months after bariatric surgery and correlate these changes with hemodynamic changes (heart rate and central and peripheral blood pressure) as well as with changes of the autonomic balance directed to heart by investigating the rate variability (HRV). Methods: Forty one patients (39 female) scheduled to be submitted to the bariatric surgery in the University Hospital were studied before and 3 and 6 months after surgery. Body fat was measured by bioimpedance. Peripheral and central blood pressure was measured with an oscillometric device or by radial applanation tonometry. A continuous digital eletrocardiographic recording (10 min) was used to determine the temporal and spectral indexes of HVR. Data expressed as mean and ± standard deviation. Statistical significance was set at P <0.05. Results: Baseline body mass index (BMI) of 43.9 ± 5.9 kg / m2. Body weight loss faster in the first 3 months and it continued with slower rate until the 6 th month after surgery with a final BMI of 33.3 ± 5.9 kg / m2. Fat mass segment at baseline was predominant in the trunk (47.0%), followed by the lower limbs (28.5%) and to a lesser extent in the upper limbs (24.5%). The fat mass relative loss was higher in the upper limbs, with less 34.5% to the 3rd postoperative month and additional loss of 29.2% to the 6 th month. Before surgery 31 of 41 patients were using antihypertensive drugs and at 3 months of the follow up only 2 volunteers were still using antihypertensive. Thus, the pressure drop was small but significant only for diastolic blood pressure (78 ± 10.3 to 72 ± 8.5 mmHg). The two HRV indexes that correlate directly with the vagal modulation of heart rate were significantly increased between the preoperative (RMSSD = 29.2 ± 20.2 ms and pNN50 = 9.7 ± 14.3 %) and 3 months, stabilizing at 6 months (RMSSD = 48.4 ± 31.2 ms and pNN50 = 23.3 ± 22.8%). A similar pattern is observed for the HF component, which increased from 32.3 ± 19.4 n.u. preoperatively to 49.5 ± 17.2 n.u. at 6 months. The LF component (in 10 arbitrary units) of HRV decreased (P <0.05) of 56.9 ± 20.9 preoperatively to 41.7 ± 18.4 at 6 months. Conclusion: The data show a reduction of the sympathetic component and increased vagal modulation component of HRV after bariatric surgery. This change of the autonomic balance to the cardiovascular system should contribute to the reduction of the heart rate and blood pressure after bariatric surgery